Workshop Pengelolaan Emosi untuk Komunitas X dengan Pendekatan Positive Psychology - Reiza, Muhammad; Putra, Davit Aditya (Universitas Negeri Gorontalo, 2025)
Emotion regulation is an essential skill in maintaining social interaction quality and psychological well-being, particularly among productive-age individuals active in community settings. This community service program aimed to enhance emotion regulation skills through a workshop based on a positive psychology approach. A quasi-experimental method with a one group pretest–posttest design was applied to 40 community members. Measurements were conducted before and after the intervention using an emotion regulation scale and analyzed through a paired sample t-test. The results indicated a significant increase in post-test scores compared to pre-test scores (p 0.001) with a very large effect size. These findings suggest that the workshop was effective in strengthening participants’ ability to recognize and manage emotional responses adaptively. The program demonstrates potential as a promotive intervention model to support psychological well-being at the community level.